Donor screening question alternatives to men who have sex with men time deferral: Potential impact on donor deferral and discomfort. Issue 1 (2nd December 2020) - O'Brien, Sheila F.; Goldman, Mindy; Robillard, Pierre; Osmond, Lori; Myhal, Geneviève; Roy, Élise
Abstract: Background: Alternative screening questions could permit low‐risk men who have sex with men (MSM) to donate blood without a time deferral. We performed a study to determine the proportion of current donors who may be deferred by various questions and their comfort with them. Study Design and Methods: Donors attending collection sites in Canada in January and February 2018 were offered one of two questionnaires but not both. Questionnaire 1 asked about risk behaviors; Questionnaire 2 rated comfort with the questions. Volunteers uncomfortable with questions participated in short qualitative telephone interviews to understand reasons. Quantitative data were analyzed using χ 2 statistics. Results: Of 36 241 donors attending, 31 904 (88%, Period 1) completed Questionnaire 1; of 34 947, a total of 30 278 (87%, Period 2) completed Questionnaire 2; 294 completed an interview. In the past 3 months 3.1% (95% confidence interval [CI], 3.1%‐3.6%) had more than one partner; 6.0% (95% CI, 5.7%‐6.2%) had a new partner; 6.7% (95% CI, 6.4%‐6.9%) were in a nonexclusive relationship; 11.2% (95% CI, 10.9%‐11.6%) had at least one of these; 3.7% (95% CI, 3.4%‐3.9%) had anal sex; and 62.8% (95% CI, 62.2%‐63.3%) had condomless sex. More than 6% were uncomfortable with each question, but more (17.2%; 95% CI, 16.8%‐17.7%) were uncomfortable with anal sex. Key reasons for discomfort were questions being too personal and unclear safety benefit. Conclusion: Most donors are comfortable answering alternative questions (except very personal ones) but question the benefit. Implementing alternative questions would result in substantive deferrals. Other policies such as using an MSM capture question to ask additional questions only to MSM should be considered.